ANALISIS BELANJA DAERAH DAN FAKTOR-FAKTOR YANG MEMPENGARUHI DI KABUPATEN BANYUMAS - Zumaeroh Zumaeroh; Agus Prabawa (Majalah Imiah Manajemen & Bisnis, 2021)
The purpose of this research are as follows was 1) to determine the effect of income tax, retribution, wealth management outcomes separated areas and other legitimate income areasof capital expendituresamount simultaneously or amount partialy, 2)to determine which variables are dominant among income tax, retribution, wealth management outcomes separated areas and other legitimate income areas of the capital expenditures. The reseacrh, which is located atKantor Dinas Pendapatan Daerah Provinsi KabupatenBanyumas and Badan Pusat Statistik KabupatenBanyumas. Data were collected analysis regression, according 1) to the income tax, retribution, wealth management outcomes separated areas and other legitimate income areas simultaneosly significant effect ofcapital expenditures and to the significant effect ofcapital expenditures, the income tax, retribution other legitimate income areas partialy significant effect of capital expenditures, That wealth management outcomes separated areas not partialy significant effect of capital expenditures, 2) to the income tax, most dominant influenceofcapital expenditures.